Device-evaluated autonomic nervous function for predicting ventricular arrhythmias and all-cause mortality in patients who underwent cardiac resynchronization therapy-defibrillator - Cheng, Chendi; Jiang, Jiang; Chen, Keping; Hua, Wei; Su, Yangang; Xu, Wei; Fan, Xiaohan; Dai, Yan; Zhang, Shu (Frontiers in Physiology, 2023)
Introduction Autonomic nervous function (ANS) function quantified by heart rate variability (HRV) was associated with long-term prognosis. By home monitoring system, this study aimed to describe the changes in ANS function among heart failure patients who underwent cardiac resynchronization therapy-defibrillator (CRT-D) implantation, as well as the possible influencing factors. To explore its predictive value for ventricular tachyarrhythmias (VTAs) and all-cause mortality. Method Patients who underwent CRT-D implantation were included. Device-measured all-day HR, night-time HR, and HRV (measured by the standard deviation of the atrial–atrial sensed intervals) were used to quantify ANS function. Multivariate Cox proportional hazards models were fitted to calculate hazard ratios (HRs) and 95% confidence intervals (CIs) of VTAs or all-cause mortality in relation to ANS function at baseline and 6 months post-implantation. The cutoff value was determined using restrictive cubic splines. Multivariable logistic regression was further established to determine factors influencing postoperative HRV. Results A total of 170 patients treated with CRT-D were eligible for analysis. During a median follow-up period of 50.8 months, 61 patients died and 69 patients experienced at least one spontaneous episode of VTAs. At 6 months after CRT implantation, 114 patients showed improvement in HRV, increasing from 66.4 ± 19.4 ms to 76.7 ± 21.2 ms. The postoperative HRV was associated with both all-cause mortality (HRs: 0.983; 95%CI: 0.968 to 0.998, p = 0.012) and VTAs (HRs: 0.973; 95%CI: 0.954 to 0.993, p = 0.008), and the relative risk would significantly increase when the postoperative HRV lower than 75ms. After adjusting for basic ANS function and possible influencing factors, patients without diabetes (p = 0.018) and with higher daily physical activity (p = 0.041) could maintain higher postoperative HRV after CRT implantation. Conclusion More than two-thirds of heart failure patients showed improvement in ANS function following CRT treatment. However, patients with diabetes and low daily physical activity levels have difficulty maintaining a higher postoperative HRV, which is associated with a worse clinical outcome.